Research progress in quality assessment methods for oocytes - TAN Yan; GONG Xuefeng; LONG Wenxiang (Yixue xinzhi zazhi, 2025)
With the decline of fertility globally, more and more infertile patients are choosing assisted reproductive technology (ART) to achieve their reproductive desires. Oocyte quality is one of the key factors affecting the success of ART. Therefore, oocyte quality evaluation has been an important research topic of ART. The most widely used evaluation method currently is the morphological assessment of oocytes, including the evaluation of intra- and extra-cytoplasmic characteristics and cell volume of oocytes. In recent years, new molecular markers, instruments, and technologies have been proposed to evaluate the oocyte quality, including mitochondrial activity, glucose-6-phosphate dehydrogenase, polarized light microscopy, molecular markers of cumulus cells and follicular fluid, time-lapse technology, and artificial intelligence. This article reviewed the morphological evaluation and emerging evaluation methods for oocyte quality assessment, providing reference for research and clinical practice related to oocyte quality assessment.